NUMERICAL INVESTIGATION OF THICKNESS AND MATERIAL EFFECTS ON THE MECHANICAL BEHAVIOR OF MILD STEEL DAMPERS USING FINITE ELEMENT ANALYSIS - Yasin, Iskandar; Sutrisno, Widarto; Hasan, Nurul; Soumi, Andi Ibrahim (Universitas Muhammadiyah Surakarta, 2026)
Mild steel dampers are widely utilized as energy dissipation devices due to their ductility and stable mechanical behavior. This study presents a numerical investigation of the effects of plate thickness and material variation on the mechanical performance of an H-type mild steel damper using nonlinear finite element analysis. The model is developed in ANSYS with three-dimensional solid elements, incorporating material and geometric nonlinearity to capture structural response under loading. Two parametric studies are conducted, including plate thickness variations (15 mm, 20 mm, 25 mm, and 30 mm) and material variations (structural steel, grey cast iron, and aluminum alloy). The mechanical behavior is evaluated based on deformation, equivalent stress, and strain distribution along the damper height. The results show that increasing plate thickness significantly reduces deformation and strain while improving stress distribution, indicating enhanced structural stiffness. However, excessive thickness may limit deformation capacity. In terms of material performance, structural steel exhibits the most stable behavior with low deformation and controlled stress and strain distribution. Aluminum shows higher deformation and strain due to its lower stiffness, while grey cast iron demonstrates limited ductility and higher stress concentration. An optimal configuration is identified at a thickness of 20-25 mm using structural steel, providing a balance between stiffness and deformation capability. These findings contribute to the design optimization of metallic dampers for structural applications.